African American Organ Donor Registration: A Mixed Methods Design Using the Theory of Planned Behavior. (September 2014) - DuBay, Derek A.; Ivankova, Nataliya; Herby, Ivan; Wynn, Theresa A.; Kohler, Connie; Berry, Beverly; Foushee, Herman; Carson, April P.; Redden, David T.; Holt, Cheryl; Siminoff, Laura; Fouad, Mona; et al.
Context: A large racial disparity exists in organ donation. Objective: To identify factors associated with becoming a registered organ donor among African Americans in Alabama. Methods: Concurrent mixed methods design guided by the Theory of Planned Behavior to analyze African Americans' decisions to become a registered organ donor by using both qualitative (focus groups) and quantitative (survey) methods. Results: The sample consisted of 22 registered organ donors and 65 nonregistered participants from 6 focus groups completed in urban (n = 3) and rural (n = 3) areas. Participants emphasized the importance of the autonomy to make one's own organ donation decision and have this decision honored posthumously. One novel barrier to becoming a registered organ donor was the perception that organs from African Americans were often unusable because of the high prevalence of chronic medical conditions such as diabetes and hypertension. Another novel theme discussed as an advantage to becoming a donor was the subsequent motivation to take responsibility for one's health. Family and friends were the most common groups of persons identified as approving and disapproving of the decision to become a donor. The most common facilitator to becoming a donor was information, whereas fear and the lack of information were the most common barriers. In contrast, religious beliefs, mistrust, and social justice themes were infrequently referenced as barriers to becoming a donor. Conclusion: Findings from this study may be useful for prioritizing organ donation community-based educational interventions in campaigns to increase donor registration.